Solar Cycle Variability of Nonmigrating Tides in the 5.3 and 15 μm Infrared Cooling of the Thermosphere (100–150 km) from SABER. Issue 3 (28th March 2019) - Nischal, N.; Oberheide, J.; Mlynczak, M. G.; Marsh, D. R.; Gan, Q.
Abstract: This paper discusses the solar cycle variation of the DE3 and DE2 nonmigrating tides in the nitric oxide (NO) 5.3 μm and carbon dioxide (CO2 ) 15 μm infrared cooling between 100 and 150 km altitude and ±40° latitude. Tidal diagnostics of SABER NO and CO2 cooling rate data (2002–2013) indicate DE3 (DE2) amplitudes during solar maximum are on the order of 1 (0.5) nW/m 3 in NO near 125 km, and on the order of 60 (30) nW/m 3 in CO2 at 100 km, which translates into roughly 15–30% relative to the monthly zonal mean. The NO cooling shows a pronounced (factor of 10) solar cycle dependence (lower during solar minimum) while the CO2 cooling does not vary much from solar min to solar max. Photochemical modeling reproduces the observed solar cycle variability and allows one to delineate the physical reasons for the observed solar flux dependence of the tides in the infrared cooling, particularly in terms of warmer/colder background temperature versus smaller/larger tidal temperatures during solar max/min, in addition to cooling rate variations due to vertical tidal advection and tidal density variations. Our results suggest that (i) tides caused by tropospheric weather impose a substantial—and in the NO 5.3 μm case solar cycle dependent—modulation of the infrared cooling, mainly due to tidal temperature, and (ii) observed tides in the infrared cooling are a suitable proxy for tidal activity including its solar cycle dependence in a part of Earth's atmosphere where direct global temperature observations are lacking. Key Points: Large solar cycle effect is seen in NO cooling rate tide due to temperature, but tidal advection shows increasing contribution over solar min CO2 cooling rate tides are more important during solar min, but NO tides become more important during solar max above 125 Tides in IR cooling rates are suitable proxy for height evolution of tidal spectrum in the thermosphere